Communication, Incentives, and the Execution of a Strategic Initiative - Hutchison-Krupat, Jeremy (Management Science, 2018)
Senior leadership has two primary levers to influence a direct report: incentives and communication. Financial incentives are credible and precisely specified but offer limited flexibility. In contrast, communication is flexible but lacks precision, and must be deemed credible to affect a direct report’s actions. We study a setting where senior leadership seeks to add a new initiative to their organization’s portfolio. The initiative’s potential to create value is not initially well understood. Senior leadership eventually obtains more precise information on the initiative’s value and subsequently may communicate this information to their direct report. We analyze senior leadership’s incentive and communication decisions, and ultimately their portfolio decision. We find that senior leadership’s communication only affects a direct report’s actions when a new initiative’s potential to create value is sufficiently uncertain. Additionally, we find instances where an organization may benefit from communication that offers lessspecificity. This paper was accepted by David Hsu, entrepreneurship and innovation.